Running worms: C. elegans self-sorting by electrotaxis - Manière, Xavier; Lebois, Félix; Matic, Ivan; Ladoux, Benoit; Di Meglio, Jean Marc; Hersen, Pascal (PLoS ONE, 2011)
The nematode C. elegans displays complex dynamical behaviors that are commonly used to identify relevant phenotypes. Although its maintenance is straightforward, sorting large populations of worms when looking for a behavioral phenotype is difficult, time consuming and hardly quantitative when done manually. Interestingly, when submitted to a moderate electric field, worms move steadily along straight trajectories. Here, we report an inexpensive method to measure worms crawling velocities and sort them within a few minutes by taking advantage of their electrotactic skills. This method allows to quantitatively measure the effect of mutations and aging on worm's crawling velocity. We also show that worms with different locomotory phenotypes can be spatially sorted, fast worms traveling away from slow ones. Group of nematodes with comparable locomotory fitness could then be isolated for further analysis. C. elegans is a growing model for neurodegenerative diseases and using electrotaxis for self-sorting can improve the high-throughput search of therapeutic bio-molecules. © 2011 Manière et al.
CRIS-Team Scopus Importer:2024-02-19